Ultrasound Applied to Subcutaneous Fat Tissue Measurements in International Elite Canoeists - Kopinski, S.; Engel, T.; Cassel, M.; Fröhlich, K.; Mayer, F.; Carlsohn, A. (International Journal of Sports Medicine, 2015)
Subcutaneous adipose tissue (SAT) measurements with ultrasound have recently been introduced to assess body fat in elite athletes. However, appropriate protocols and data on various groups of athletes are missing. We investigated intra-rater reliability of SAT measurements using ultrasound in elite canoe athletes. 25 international level canoeists (18 male, 7 female; 23±4 years; 81±11 kg; 1.83±0.09 m; 20±3 training h/wk) were measured on 2 consecutive days. SAT was assessed with B-mode ultrasound at 8 sites (ISAK): triceps, subscapular, biceps, iliac crest, supraspinal, abdominal, front thigh, medial calf, and quantified using image analysis software. Data was analyzed descriptively (mean±SD, [range]). Coefficient of variation (CV%), intraclass correlation coefficient (ICC, 2.1) and absolute (LoA) and ratio limits of agreement (RLoA) were calculated for day-to-day reliability. Mean sum of SAT thickness was 30.0±19.4 mm [8.0, 80.1 mm], with 3.9±1.8 mm [1.2 mm subscapular, 8.0 mm abdominal] for individual sites. CV for the sum of sites was 4.7%, ICC 0.99, LoA 1.7±3.6 mm, RLoA 0.940 ( *  /÷1.155). Measuring SAT with ultrasound has proved to have excellent day-to-day reliability in elite canoe athletes. Recommendations for standardization of the method will further increase accuracy and reproducibility.
Keywords: subcutaneous adipose tissue; skinfold thickness; elite athletes; body composition; ultrasonography